Selling transit: perception, participation, and the politics of transit in Kansas City, Missouri - Wood, James Patrick (Kansas State University, 2014)
Informed and robust stakeholder participation in the transit-planning process gives residents and communities a remarkable opportunity to take ownership of the shaping of their city’s future form and function, and allows planners to design transit networks that serve the full range of citizen needs. Therefore, the degree to which citizens are permitted to participate in the formation of a city’s transit plan has a significant influence on both its final design and its subsequent adoption by civic and political leaders. Concurrent with the influence of citizen input is the role of political strategy, since many urban transit plans must meet voter approval and a poorly-run political campaign can sink even the most substantial of transit plans. In seeking to analyze both the role of public participation and the role of campaign strategy, this study employs descriptive historical research and stakeholder surveys to assess the impact and perceived importance of inclusive design practices, as well as the political impact of a transit campaign’s general strategy, on the voter approval of transit-related ballot initiatives in Kansas City, Missouri. There are two central implications of this project. One is that the failure of transportation planners and civic activists in Kansas City to accommodate the wishes and input of diverse groups of residents and community leaders in the planning process has led to repeated defeats whenever said plans are presented to Kansas City voters for approval. The other is that urban politics and campaign strategies play a larger role in selling transit proposals than many leading figures in Kansas City have realized, and that the city’s unique political and geographic structure requires a more nuanced and technologically-diverse approach to voter persuasion than has been applied thus far. It can be theorized that reversing both of these trends will increase the likelihood of future voter approval of transportation initiatives. In addition to a political and historical analysis of transit in Kansas City, this study seeks to examine whether deliberate public participation in the transportation planning process has a direct impact on citizen support for transportation-related ballot initiatives in Kansas City.
Keywords: Transit; Public participation; Transit elections; Urban politics; Transit planning; Kansas City; Public Policy and Social Welfare (0630); Transportation (0709); Urban Planning (0999)